Contemporary Latin America : 1970 to the present - Holden, Robert H.; Villars, Rina. (Chichester, West Sussex, UK : Wiley-Blackwell, a John Wiley & Sons, Ltd. publication, 2013)
"Contemporary Latin America presents the epochal political, economic, social, and cultural changes in Latin America over the last 40 years and comprehensively examines their impact on life in the region, and beyond. Provides a fresh approach and a new interpretation of the seismic changes of the last 40 years in Latin America. Introduces major themes from a humanistic and universal perspective, putting each subject in a context that readers can understand and relate to. Focuses on 'Ibero-America'--Brazil and the eighteen countries that were formerly Spanish possessions--while offering valuable comparative views of the non-Iberian areas of the Caribbean. Emphasizes the global, regional and national dimensions of the region's recent past"--
"Provides a fresh approach and a new interpretation of the seismic changes of the last 40 years in Latin America"--
What is Latin America? -- Beliefs -- The demise of social revolution -- The armed forces bow to civilian rule -- The turning toward democracy -- Religion, politics and the state -- Lawless violence, impunity and the democratic transition -- The challenge of sustained growth -- Poor countries, rich countries -- Agonies of underdevelopment -- Education -- Research and communications -- Literature and the visual arts -- Cinema and sports -- The family women and sexuality -- Indigenous peoples and their movements -- Toward a Latin American community of nations?
Includes bibliographical references and index.
Keywords: Latin America -- History -- 1980-; Latin America -- History -- 20th century; Latin America -- History -- 1980-; Latin America -- History -- 20th century; Latin America; Since 1900; History